NanoSIMS sulfur isotopic analysis at 100 nm scale by imaging technique - Hao, Jia-Long; Zhang, Liu-Ping; Yang, Wei; Li, Zhao-Yang; Li, Rui-Ying; Hu, Sen; Lin, Yang-Ting (Frontiers in Chemistry, 2023)
NanoSIMS has been widely used for in-situ sulfur isotopic analysis (32S and 34S) of micron-sized grains or complex zoning in sulfide in terrestrial and extraterrestrial samples. However, the conventional spot mode analysis is restricted by depth effects at the spatial resolution < 0.5–1 μm. Thus sufficient signal amount cannot be achieved due to limited analytical depths, resulting in low analytical precision (1.5‰). Here we report a new method that simultaneously improves spatial resolution and precision of sulfur isotopic analysis based on the NanoSIMS imaging mode. This method uses a long acquisition time (e.g., 3 h) for each analytical area to obtain sufficient signal amount, rastered with the Cs+ primary beam of ∼100 nm in diameter. Due to the high acquisition time, primary ion beam (FCP) intensity drifting and quasi-simultaneous arrival (QSA) significantly affects the sulfur isotopic measurement of secondary ion images. Therefore, the interpolation correction was used to eliminate the effect of FCP intensity variation, and the coefficients for the QSA correction were determined with sulfide isotopic standards. Then, the sulfur isotopic composition was acquired by the segmentation and calculation of the calibrated isotopic images. The optimal spatial resolution of ∼ 100 nm (Sampling volume of 5 nm × 1.5 μm2) for sulfur isotopic analysis can be implemented with an analytical precision of ∼1‰ (1SD). Our study demonstrates that imaging analysis is superior to spot-mode analysis in irregular analytical areas where relatively high spatial resolution and precision are required and may be widely applied to other isotopic analyses.